Elevated Percentage of CD3+ T-Cells and CD4+/CD8+ Ratios in Multiple System Atrophy Patients - Cao, Bei; Chen, Xueping; Zhang, Lingyu; Wei, Qianqian; Liu, Hui; Feng, Weihua; Chen, Yongping; Shang, Huifang (Frontiers in Neurology, 2020)
α-synuclein is involved in the pathogenesis of multiple system atrophy (MSA) and can be regulated by peripheral immune activation (PIA). We aimed to clarify the correlations between PIA and the prevalence of MSA and to analyze the role of PIA in the progression of the disease. A total of 321 patients with probable MSA and 321 age- and gender-matched healthy controls were included in this study. Lymphocyte subsets, including CD3+, CD4+, and CD8+ cells, and the levels of immunoglobulins IgG, IgM, and IgA were evaluated. The proportions of CD3+ and CD4+ T-lymphocytes were significantly increased in MSA patients compared with those of normal controls. In addition, the ratio of CD4+ to CD8+ cells was significantly increased in male MSA patients and IgG concentrations were decreased in female MSA patients. Furthermore, the concentrations of IgM in female MSA patients were dynamically different at various disease stages and gradually decreased from the early stage until the end stage of the disease (p = 0.029). Other detected immunological indexes were not significantly different during the entire disease course. In this study, high proportions of CD3+ and CD4+ T-lymphocytes and decreased IgG levels were associated with an increased risk for MSA in a Chinese patient population. In addition, PIA may be involved in the progression of MSA.